2021
DOI: 10.2519/jospt.2021.10491
|View full text |Cite
|
Sign up to set email alerts
|

The Unknown Prevalence of Postrandomization Bias in 15 Physical Therapy Journals: A Methods Review

Abstract: Objectives To determine the prevalence of prospective clinical trial registration and postrandomization bias in published musculoskeletal physical therapy randomized clinical trials (RCTs). Design A methods review. Literature Search Articles indexed in MEDLINE and published between January 2016 and July 2020 were included. Study Selection Criteria Two independent blinded reviewers identified the RCTs using Covidence. We included RCTs related to musculoskeletal interventions that were published in International… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 90 publications
0
16
1
Order By: Relevance
“…A 2021 methodological SR of RCTs involving musculoskeletal physical therapy interventions published in ISPJE member journals demonstrated that it could not be determined if researchers followed their original research question, followed their methods, or reported their study consistent with the established research record 64.5% (89/138) of the time [7]. This was secondary to the RCTs being retrospectively registered, unregistered, or having unclear registrations.…”
Section: Problems With Post-randomization Biasesmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2021 methodological SR of RCTs involving musculoskeletal physical therapy interventions published in ISPJE member journals demonstrated that it could not be determined if researchers followed their original research question, followed their methods, or reported their study consistent with the established research record 64.5% (89/138) of the time [7]. This was secondary to the RCTs being retrospectively registered, unregistered, or having unclear registrations.…”
Section: Problems With Post-randomization Biasesmentioning
confidence: 99%
“…This was secondary to the RCTs being retrospectively registered, unregistered, or having unclear registrations. Furthermore, of the ISPJE member journals that required prospective clinical trial registration, it was established that 8.2% (4/49) of the RCTs changed their primary research question, and 16.3% (8/49) changed their primary outcome measures [7]. In addition, four of these questionable publications were rated as having Physiotherapy Evidence Database (PEDro) scores of 7-8/10 [7].…”
Section: Problems With Post-randomization Biasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall quality and transparency of clinical research has also been called into question 7,8,23–28 . This is important because clinicians rely not only on the results from clinical trials but also on details of the trial related to generalizability in their own settings.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing adherence to checklists and guidelines for the conduct and reporting of research is a significant step toward monitoring the profession's strides toward high‐quality, transparent and reproducible research. A review of randomized controlled trials (RCTs) focusing only on musculoskeletal physiotherapy interventions reported that a mere third of selected RCTs were consistent with their pretrial registration 28 . Whether these findings can be extrapolated to other types of interventions or related to other areas of research is unknown and should be investigated.…”
Section: Introductionmentioning
confidence: 99%